Effect of a high dose atorvastatin as adjuvant therapy to mesalamine in attenuating inflammation and symptoms in patients with ulcerative colitis: a randomized controlled pilot study - Alarfaj, Sumaiah J.; El-Haggar, Sahar M.; Hegazy, Sahar K.; Maher, Maha M.; Bahgat, Monir M.; Elmasry, Thanaa A.; Alrubia, Sarah; Alsegiani, Amsha S.; Bahaa, Mostafa M. (Frontiers in Medicine, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory disorder of the colon. Several preclinical studies investigated the beneficial effects of atorvastatin in colitis. Activation of sphingosine 1 phosphate (S1P)/ tumor necrosis factor-alpha (TNF-α)/ interleukin-6 (IL-6) pathways has been confirmed in the pathogenesis of UC and preclinical studies proved the efficacy of atorvastatin on these pathways.AimTo investigate the role of atorvastatin on S1P/TNF-α/IL-6 pathway in UC.MethodsPatients with mild to moderate UC were allocated into two groups in this pilot study. For 6 months, Group 1 (placebo group) received both a placebo and 1 g of mesalamine three times daily (t.i.d.). Group 2, (the atorvastatin group) received atorvastatin 80 mg once daily and 1 g of mesalamine t.i.d. A gastroenterologist evaluated the patients’ colitis severity by partial Mayo score index (PMS). Serum IL-6, S1P, TNF-α, nitric oxide (NO), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and fecal calprotectin were measured before and after treatment. Short Form 36 questionnaire (SF-36) was also assessed. A clinical response was defined as a decline in the rectal bleeding sub score of at least one point, and a decrease in PMS of at least two points. Clinical remission was defined as a PMS of less than 2 and the absence of any single sub score greater than 1.Primary outcomeDecreased PMS and improved quality of life.Secondary outcomeChange in the level of measured biomarkers.ResultsCompared to the placebo group (n = 24), the atorvastatin group (n = 23) exhibited a significant decrease in the level of IL-6 (p = 0.001), S1P (p = 0.0001), TNF-α (p = 0.003), NO (p = 0.0001), CRP (p = 0.015), ESR (p = 0.012), PMS (p = 0.013), and fecal calprotectin (p = 0.0003), and improved SF-36 (p = 0.006). In placebo group, the response rate was 83.33% (n = 20/24) for PMS, and the remission rate was 45.83% (n = 11/24). In the atorvastatin group, the response rate was 91.3% (n = 21/23), and the remission rate was 60.8% (n = 14/23) for PMS.ConclusionAtorvastatin could be an adjunctive therapy for patients with UC.Clinical trial registrationhttps://www.clinicaltrials.gov/, Identifier NCT05561062.